P047: Frailty assessment to help predict patients at risk of ED-induced delirium. (2nd June 2016) - Giroux, M.; Boucher, V.; Émond, M.; Sirois, M.; Daoust, R.; Gouin, E.; Pelletier, M.; Berthelot, S.; Voyer, P.; Moore, L.; Lemire, S.; Lamontagne, M.; et al.
Abstract : Introduction: Delirium is a frequent complication among seniors in the emergency department (ED). This condition is often underdiagnosed by ED professionals even though it is associated with functional & cognitive decline, longer hospital length of stay, institutionalization and death. Frailty is increasingly recognized as an independent predictor of adverse events in seniors and screening for frailty in EDs has recently been recommended. The aim of this study was to assess if screening seniors for frailty in EDs could help identify those at risk of ED-induced delirium.Methods: This study is part of the Incidence and Impact measurement of Delirium Induced by ED-Stay study, an ongoing multicenter prospective cohort study in 5 Quebec EDs. Patients were recruited after 8 hours in the ED exposure & followed up to 24h after ward admission. Frailty was assessed at ED admission using the Canadian Study of Health and Aging-Clinical Frailty Scale (CSHA-CFS) which classified seniors from robust (1/7) to severely frail (7/7). Seniors with CSHA-CFS ≥ 5/7 were considered frail. Delirium was assessed using the Confusion assessment method and Delirium Index.Results: Of the 380 patients recruited, mean age was 76.5 (±8.9). Male were 50%. Mean stay in the ED was 1.4 day (±0.82). Preliminary data show an incidence of ED-induced delirium of 8.4%. Average frailty score at baseline was 3.5/7. 72 patients were considered frail, while 289 were considered robust. Among the frail seniors, there were 48.4% (30-66%) patients with ED-induced delirium vs 17.9% (13.7-22.0] in the non-frail ones (p<0.0001).Conclusion: Increased frailty appears to be associated with increased ED-induced delirium. Screening for frailty at emergency triage could help ED professionals identify seniors at higher risk of ED-induced delirium. Further studies are required to confirm the importance of the association between frailty and ED-induced delirium